pengembangan textbook: introduction to text types and analysis di prodi pendidikan bahasa inggris ftik unisnu jepara - Hayu Dian Yulistianti (Jurnal Lingua Idea, 2017)
In the process of teaching and learning, as a teacher need a handbook to guide students in learning materials. The objectives of the research are to develop a textbook for teaching material in the course of Introduction to Text Types in accordance with the quality, criteria and also to improve the quality of teaching and learning process. The quality of a textbook has to focus on students' understanding in the material, teachers can easily convey the material in detail. Syllabus and lesson plan of the course is used as references in developing materials. There are several steps in developing a textbook, such as: planning, organizing, implementation and evaluation. The result of measurement from the reviewers based on categories has 40.33 in average score. It came out based on several aspects, such as: the concept of truth, clarity sentence, linguistic, evaluation, enforceability, handouts structure, physical appearance and references. The practically test was done by the students got 113 in average score. It shows that criterian of textbook is excellent to use in the course of Introduction to Text Types, English Department of FTIK UNISNU Jepara.